Analyzing Figurative Language Utilized in Chosen Song Lyrics by Eminem - Kholilullah, Muhammad Faiz (Nexus Publishing NXP, 2023)
Figurative language offers expressive alternatives to literal expression, enriching communication through non-literal phrases that convey deeper meanings. This study explores the analysis of figurative language within Eminem’s song “Mockingbird”, aiming to identify various types of figurative language and their contextual significance. The data source comprises the lyrics of “Mockingbird”, a rap song released on November 12, 2004. Employing a descriptive qualitative research design, the study utilizes document analysis to categorize and interpret figurative language types and their meanings in the song. The research identifies nine types of figurative language present in “Mockingbird”: metaphor, simile, symbol, personification, metonymy, allegory, hyperbole, and irony. Supporting the analysis are pertinent references and theoretical frameworks related to figurative language. Twenty-five instances from the song were selected for in-depth analysis: 2 metaphors, 5 similes, 3 symbols, 1 personification, 4 metonymies, 1 allegory, 6 hyperboles, and 3 instances of irony. The findings classify and thoroughly examine each type of figurative language used by Eminem in the song. This study aims to contribute significantly by enhancing readers’ understanding of figurative language, thereby elucidating contextual meanings and introducing new English vocabulary applicable in everyday conversations. It endeavors to facilitate fluency in English language usage among learners and enthusiasts alike, fostering a deeper appreciation for the artistry and communicative power of figurative expression.